2019
DOI: 10.1039/c8tc04171g
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth-free composites of carbon dots/metal–organic frameworks as white light emitting phosphors

Abstract: Here we report a new type of white light-emission material that is free of rare earth metals, fabricated by conveniently compositing carbon dots (CDs) with Zr(iv)-based metal–organic frameworks (MOFs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…In [ 85 ] it was demonstrated that choosing the adequate ratio between CDs and starch particles effectively prevented self-quenching and resulted in a significant increase of the PL QY compared with bare CDs deposited on a glass. Another materials used as a matrix for CDs are metal–organic framework (MOF): Zr(IV)-based MOF was used to design CD-based composites with white emission and high PL QY reaching 37% [ 96 ].…”
Section: Improvements Of Optical Properties Of Cdsmentioning
confidence: 99%
“…In [ 85 ] it was demonstrated that choosing the adequate ratio between CDs and starch particles effectively prevented self-quenching and resulted in a significant increase of the PL QY compared with bare CDs deposited on a glass. Another materials used as a matrix for CDs are metal–organic framework (MOF): Zr(IV)-based MOF was used to design CD-based composites with white emission and high PL QY reaching 37% [ 96 ].…”
Section: Improvements Of Optical Properties Of Cdsmentioning
confidence: 99%
“…14 Wang et al designed a MOF material from CDs and Zr(IV) with white emission at 365 nm excitation with a PLQY of 37%, and fabricated a WLED with a power efficiency of 1.7 lm W À1 . 15 Shen et al embedded CDs in trisodium citrate crystals to prepare a green emissive phosphor with a PLQY of 21%, and fabricated a WLED with a power efficiency of 6.9 lm W À1 . 16 We combined CDs with starch, polyvinylalcohol, BaSO 4 , NaCl, sodium silicate, silica and branched polyethylenimine to prepare phosphors with PLQYs ranging from 26% to 60%, [17][18][19][20][21][22][23] and WLEDs with power efficiencies in the range of 8-28 lm W À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The report stated that the CIE coordinates were (0.31, 0.34), the CRI was 82, and the LE was 1.7 lm W −1 . [ 152 ] Additionally, Wang et al encapsulated R‐phycoerythrin into HSB‐W1 MOFs. Although the protein was denatured after insertion, it showed dual fluorescence emission at 518 and 600 nm.…”
Section: Recent Progress In Mof Materials For Wledsmentioning
confidence: 99%